(untitled) (Research, Society and Development, 2022)
Tuberculosis (TB) is an infectious disease caused by a bacterium called Mycobacterium tuberculosis, also known as Koch’s Bacillus. Although there was a tendency to decrease the incidence of this pathology in Brazil, between the years 2010-2016, such data showed significant growth again during the period 2017-2018. Therefore, the objective of this work was to analyze the confirmed cases of TB among the constituent municipalities of the micro-region of Alagoinhas-BA, between the years 2018-2022. For this, an ecological, observational, retrospective and descriptive study was carried out, whose data were obtained from the electronic address of the Information System of Notifiable Diseases of the Unified Health System (SINANWEB/SUS), in search of indicators of this disease in the region. described. Among the results presented, from the total of 259 confirmed notifications, there was a higher prevalence in the municipality of Alagoinhas, with 172 (66.4%) cases. Through this study, it is possible to establish a presentation to the scientific community about the epidemiological scenario of positive records for tuberculosis in such localities, a subject that remains with a low number of published works. In this way, the results presented can be considered by public agencies when making decisions regarding state and municipal public health.